A novel role for protein tyrosine phosphatase 1B as a positive regulator of neuroinflammation. Issue 1 (December 2016) - Song, Gyun; Jung, Myungsu; Kim, Jong-Heon; Park, Hana; Rahman, Md; Zhang, Sheng; Zhang, Zhong-Yin; Park, Dong; Kook, Hyun; Lee, In-Kyu; Suk, Kyoungho
Abstract Background Protein tyrosine phosphatase 1B (PTP1B) is a member of the non-transmembrane phosphotyrosine phosphatase family. Recently, PTP1B has been proposed to be a novel target of anti-cancer and anti-diabetic drugs. However, the role of PTP1B in the central nervous system is not clearly understood. Therefore, in this study, we sought to define PTP1B's role in brain inflammation. Methods PTP1B messenger RNA (mRNA) and protein expression levels were examined in mouse brain and microglial cells after LPS treatment using RT-PCR and western blotting. Pharmacological inhibitors of PTP1B, NF-κB, and Src kinase were used to analyze these signal transduction pathways in microglia. A Griess reaction protocol was used to determine nitric oxide (NO) concentrations in primary microglia cultures and microglial cell lines. Proinflammatory cytokine production was measured by RT-PCR. Western blotting was used to assess Src phosphorylation levels. Immunostaining for Iba-1 was used to determine microglial activation in the mouse brain. Results PTP1B expression levels were significantly increased in the brain 24 h after LPS injection, suggesting a functional role for PTP1B in brain inflammation. Microglial cells overexpressing PTP1B exhibited an enhanced production of NO and gene expression levels of TNF-α, iNOS, and IL-6 following LPS exposure, suggesting that PTP1B potentiates the microglial proinflammatory response. To confirm the role of PTP1B in neuroinflammation, we employed a highly potent and selective inhibitor of PTP1B (PTP1Bi). In LPS- or TNF-α-stimulated microglial cells, in vitro blockade of PTP1B activity using PTP1Bi markedly attenuated NO production. PTP1Bi also suppressed the expression levels of iNOS, COX-2, TNF-α, and IL-1β. PTP1B activated Src by dephosphorylating the Src protein at a negative regulatory site. PTP1B-mediated Src activation led to an enhanced proinflammatory response in the microglial cells. An intracerebroventricular injection of PTP1Bi significantly attenuated microglial activation in the hippocampus and cortex of LPS-injected mice compared to vehicle-injected mice. The gene expression levels of proinflammatory cytokines were also significantly suppressed in the brain by a PTP1Bi injection. Together, these data suggest that PTP1Bi has an anti-inflammatory effect in a mouse model of neuroinflammation. Conclusions This study demonstrates that PTP1B is an important positive regulator of neuroinflammation and is a promising therapeutic target for neuroinflammatory and neurodegenerative diseases.